Analisis Desain Visual Google Doodle Seniman Indonesia - Prasetyo, Abdul Rahman (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2023)
Illustrations of Google Doodles with the theme of Indonesian culture attract attention. One of them is a Google Doodle with the theme of illustrations by Indonesian artists. This study aims to: 1) Analyze the visualization of 3 Google Doodle illustrations by Bagong Kussudiardja, Tino Sidin and Affandi in terms of illustration form, color, and typography. 2) Analyze Google Doodle Bagong Kussudiardja, Tino Sidin and Affandi's illustrations with their meaning and content. The type of research used in this research is to use a qualitative descriptive approach because I want to examine more deeply and describe the Google Doodle visuals with the theme of Indonesian Artists. In the data analysis technique in this study using the interactive model method proposed by Miles and Huberman which has the stages of Data Source, Data Reduction, Data Presentation, and Data Withdrawal. The subject of this study used several visual illustrations from 3 Google Doodle illustration works, namely Bagong Kussudiardja, Affandi, and Tino Sidin. The results of this study indicate that there are 2 types of illustrations, namely Benyamin Sueb's Google Doodle and Affandi's Google Doodle including imaginary illustrations and Tino Sidin's Google Doodle including cartoon illustrations. The use of illustration shapes, colors, and typography in these three Google Doodle illustrations has its own meanings in each illustration, and of course it is related to the content of the theme raised in each of these three Google Doodle illustrations. The typography of the three Google Doodle illustrations uses the Sans Serif font family with the Custom Decorative Font typeface. The selected font characters in the three Google Doodle illustrations tend to match the themes raised in each Google Doodle illustration.